Report on National Agriculture Innovation Project (NAIP) - Planning Commission (Planning Commission Government of India, 2009)
The National Agriculture Innovation Project (NAIP), launched in 2006, seeks to transform India’s agricultural sector by promoting research-driven, knowledge-based innovation to address stagnating productivity, resource pressures, and rural livelihood challenges. With a total budget of $250 million funded by the World Bank and the Government of India, NAIP emphasizes capacity building within ICAR and State Agricultural Universities, integration of production-to-consumption systems, and livelihood improvements for rural populations. The project operates through a consortium-based management structure, engaging multiple research institutions and local partners, and has initiated numerous sub-projects benefiting over 132,000 individuals. Key components include multidisciplinary research, value chain innovations, ICT-based knowledge dissemination, and sustainable farming practices. Early outcomes highlight the effectiveness of decentralized governance, stakeholder collaboration, and adaptive learning. NAIP aims to modernize India’s agricultural framework, enhancing productivity, market competitiveness, and rural welfare, while ensuring sustainable management of natural resources.
Planning Commission of India Government of India
Keywords: National Agriculture Innovation Project; Agricultural Research; ICAR; Livelihood Security; Sustainable Agriculture; Value Chain; Technology Integration; Farmer-Centric Innovations; State Agricultural Universities; Consortium Approach; Post-Harvest Management; Food Security